Knowledge engineering shells - Bourbakis, Nikolaos G (World Scientific, 1993)
Includes bibliographical references.; This book offers a systematic approach to knowledge engineering problems. It gives a brief overview of knowledge engineering systems and environments, covering both classical and recent techniques of the design and evaluation of them. Detailed descriptions of particular techniques and applications are also provided; Quỹ Châu Á